Menimbang Manfaat dan Kerugian Investasi Saham dan Kripto Bagi Pelaku Pasar Indonesia - Rolando, Benediktus; Al-Amin, Al-Amin; Rahmat, Rahmat; Zuwardi, Zuwardi; Izmuddin, Iiz (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
This study aims to weigh the benefits and disadvantages of stock and crypto investments for Indonesian market participants. This study uses a desk study approach by reviewing relevant literature from various sources. Various articles, scientific journals, and research reports are used to provide a detailed overview of the characteristics of stock and crypto investments, including their potential benefits and risks. Stocks are known to have a more stable regulatory foundation and are often considered a safer long-term investment. On the other hand, crypto offers the potential for high returns with greater volatility, making it attractive to high-risk investors. However, crypto also faces significant regulatory and security challenges. The results of this study are expected to provide insights for Indonesian investors in making more informed and measured investment decisions. It's hoped that by understanding the dynamics and characteristics of both, investors can be wiser in choosing investment options that suit their risk profile and financial goals.